HPV vaccination in Latin America: Coverage status, implementation challenges and strategies to overcome it - Nogueira-Rodrigues, Angélica; Flores, Matheus Gonçalves; Macedo Neto, Avelar Oliveira; Braga, Lucélia Antunes Coutinho; Vieira, Carolina Martins; Sousa-Lima, Renata Maria de; de Andrade, Diocésio Alves Pinto; Machado, Karime Kalil; Guimarães, Andrea Paiva Gadelha (Frontiers in Oncology, 2022)
Cervical cancer remains a leading cause of morbidity and mortality amongst females in Latin America (LATAM). Cervical cancer is a preventable disease and HPV vaccination is a main key strategy towards its elimination. This study analyzes HPV vaccine implementation current status and the main barriers to achieve adequate coverage in the region. Data from the nineteen sovereign states of LATAM (comprised of all Portuguese and Spanish-speaking nations located south of the United States) were collected, including year of HPV vaccine implementation, gender and age targets, the number of doses included in the public program and coverage by dose. Sixteen out of the 19 evaluated countries have already implemented HPV vaccination programs. However, despite its proven efficacy and safety, HPV vaccine uptake in LATAM has been lower than expected. There is an evident decline in adhesion, mainly regarding the second dose. Several reasons are probably involved, of note: limited knowledge of HPV and HPV vaccine, misguided safety concerns, high cost, cultural barriers, and the Covid19 pandemic. Proper strategies to overcome these barriers are needed to ensure successful uptake. Effective policies are: adopting the one dose schedule, delivering the vaccine on both health center and schools, and advising health professionals to recommend the vaccine. Further research regarding HPV vaccine hesitancy in Latin America is needed.